Esophageal transit time assessed by magnetic methods: An in vitro feasibility study of the novel alternating current biosusceptometry with 3-axis magnetorresistor - Paixao, F. C. [UNESP] (2013)
A hybrid magnetic instrumentation to detect a magnetic field from a permanent magnet, and to detect magnetic markers and tracers using alternating current biosusceptometry (ACB) is discussed. The instrument was used to in vitro evaluation of the esophageal transit time. The sensitivity between both magnetic methods was compared, showing sensitivity for in vivo applications. © 2013 Springer-Verlag.